2006
DOI: 10.1037/1076-898x.12.2.96
|View full text |Cite
|
Sign up to set email alerts
|

Emotional intelligence, personality, and task-induced stress.

Abstract: Emotional intelligence (EI) may predict stress responses and coping strategies in a variety of applied settings. This study compares EI and the personality factors of the Five Factor Model (FFM) as predictors of task-induced stress responses. Participants (N = 200) were randomly assigned to 1 of 4 task conditions, 3 of which were designed to be stressful. Results confirmed that low EI was related to worry states and avoidance coping, even with the FFM statistically controlled. However, EI was not specifically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
151
1
11

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 198 publications
(194 citation statements)
references
References 44 publications
21
151
1
11
Order By: Relevance
“…Both Matthews et al (2006) and Peters, Kranzler, and Rossen (2009) found that MSCEIT scores showed a negative relationship with emotion-focused coping (r = -.19 and -.46, respectively) and no relationship with problem-focused coping. Matthews et al also found a small negative relationship with avoidance-focused coping (r = -.16).…”
Section: Coping and Emotional Intelligencementioning
confidence: 99%
“…Both Matthews et al (2006) and Peters, Kranzler, and Rossen (2009) found that MSCEIT scores showed a negative relationship with emotion-focused coping (r = -.19 and -.46, respectively) and no relationship with problem-focused coping. Matthews et al also found a small negative relationship with avoidance-focused coping (r = -.16).…”
Section: Coping and Emotional Intelligencementioning
confidence: 99%
“…Whilst there is some evidence to suggest that 'trait' EI may operate as a protective resource within stress-illness processes (e.g., Mikolajczak, Roy, Luminet, Fillée, & de Timary, 2007), the role of 'ability' EI in this regard appears unclear (e.g., Matthews et al, 2006). Moreover, few studies have simultaneously examined relations between EI, chronic stressors and mental health in adolescents.…”
mentioning
confidence: 99%
“…Medical imaging professionals (e.g., radiologists, technologists) differ in a variety of ways, including clinical experience, education and training, demographics (e.g., age, gender), and specific job requirements. In addition to these more obvious sources of variability, other (often unnoticed) factors contribute to inter-observer variability including technology proclivity, personality [13], intelligence, emotional state, and sensory/motor skills ( Table 1). All of these variables contribute in varying degrees to the collective attributes and characteristics of individual end users and should be considered when attempting to understand and quantify occupational stress and fatigue.…”
Section: Creating a Customizable Profiling Systemmentioning
confidence: 99%